Towards automatic modeling of volleyball players` behavior for analysis, feedback, and hybrid training - Salim, F. A.; Haider, F.; Postma, D.; van Delden, R.; Reidsma, D.; Luz, S.; van Beijnum, B.-J. (Journal for the Measurement of Physical Behaviour, 2020)
Coaches and players desire and would benefit greatly from easy access to performance data of matches and training sessions (Koekoek, van der Mars, van der Kamp, Walinga, & van Hilvoorde, 2018). They use this information not only to monitor performance but also to plan training programs and game strategy. According to the assessment of volleyball coaches in The Netherlands,1 the two areas which can substantially improve sports training are as follows: